Roman Pollak i życie literackie w Poznaniu w świetle dokumentacji archiwalnej - Przybyszewska, Alicja (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article presents the link between Roman Pollak and Poznan’s literary community in the interwar and postwar periods, and is based on the source material found in the professor’s correspondence and the documents found in the Raczyński Library in Poznan. It focuses on Roman Pollak’s relationship with Kazimiera Iłłakowiczówna, his involvement in research into the links between Poznan and Jan Kasprowicz’s works, and on the contacts that he maintained with the graduates of the university who were actively engaged in the literary community, e.g. Apolonia Załuska-Strömberg, a translator of Scandinavian literature. All of these aspects attest to Roman Pollak’s interest in the life and careers of his former students and his support of their literary and publishing aspirations.